ESTIMASI NILAI EKONOMI AIR IRIGASI DAN STRATEGI PEMANFAATANNYA DALAM PENENTUAN IURAN IRIGASI - SUMARYANTO -; BONAR M. SINAGA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
The study is aimed to valuate irrigation water and to assess its prospect forwater pricing strategy, and implication of optimal cropping pattern on farm's incomeand rice production. Mathematical programming is applied for the valuation. Strategyof water pricing based on the reconciling efficiency and equity concern. Results of thestudy show that shadow price of irrigation water were equal to zero on December–Mayand positive on June–November. Within the positive period, the lowest and highestprices were taken place on June and September respectively. Monthly average of theshadow price was Rp. 40 700/(l/sec), which is equivalent with Rp. 15.75/m3. It isfeasible to apply the shadow price for determining ceiling rate of irrigation watercharges. Potential method of water pricing is combination of per unit area in wet seasonand per crop pricing in dry season. Implementation of optimal cropping pattern as wellas water pricing was potential to improve both farm's income and irrigation efficiency,but disincentive to increase rice production.